Sexual activity based fears during pregnancy, sexual function and dyadic adjustment in couples who are expecting their first child. (3rd April 2022) - de Pierrepont, Catherine; Brassard, Audrey; Bécotte, Katherine; Lessard, Isabelle; Polomeno, Viola; Péloquin, Katherine
Abstract: Purpose: Sexual activity based fears during pregnancy are common, but very few studies have examined their association with relationship variables. Secondary analysis of associations between these fears during pregnancy and both partners' sexual function and dyadic adjustment were conducted. Materials and Methods: A sample of 67 French-Canadian first-time parenting couples living in Ontario completed online questionnaires on sexual activity based fears, sexual function, and dyadic adjustment as experienced during pregnancy. Results: While one-third of participants reported no fears, other couples experienced one to six fears, the two most common fears among partners being inducing labor and causing a miscarriage. Dyadic path analyses supported indirect associations between sexual activity based fears and lower dyadic adjustment via poorer sexual function. During pregnancy, these fears in women and men are associated with poorer dyadic adjustment in both partners through the women's poorer sexual function. Conclusion: These findings suggest including prenatal sexual activity based fears in perinatal sexuality counseling, education, and interventions.